PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON ASSET, PRICE TO BOOK VALUE, DAN PRICE EARNING RATIO TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2014-2015 - Saraswati, Adestia; Halim, Abdul; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2019)
This study aims to examine and explain the effect of partial and dominant Earning Per Share (EPS), Debt to Equity Ratio (DER), Return On Assets (ROA), Price to Book Value (PBV) and Price Earning Ratio (PER) on return shares of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The analytical method used in this study is a quantitative method by testing classical assumptions and statistical analysis, namely multiple linear regression analysis. The sampling method used was purposive sampling. The variables of this study consisted of EPS, DER, ROA, PBV and PER as independent variables, and stock returns as the dependent variable with a total sample of 36 manufacturing companies. The analysis shows that EPS, DER, PBV and PER affect stock returns while ROA does not affect stock returns. For further research, it is expected to be able to add other research variables such as Net Profit Margin and Current Ratio.